P042 APL expression is down-regulated in an animal model of chronic colitis. (25th January 2019) - Nagaishi, T; Kojima, Y; Yamada, D; Watabe, T; Tsugawa, N; Jose, N; Onizawa, M; Watanabe, M
Abstract: Background: Apelin (APL), originally isolated from alimentary tract, has been defined as the endogenous ligand for APJ, which is a known G protein-coupled receptor. It has been reported that APL is up-regulated in the colonic tissues of murine model of dextran sodium sulphate (DSS)-induced acute colitis, and it is suggested to be associated with the pathogenesis of inflammatory bowel diseases (IBD), such as Crohn's disease and ulcerative colitis, in humans. However, the mechanism and function of APL in the context of IBD are still not well understood. Here, we analysed APL expression in the murine model of chronic colitis. Methods: Each cell type in the colonic tissue, including epithelial cells and lamina propria lymphocytes, were first isolated from wild-type C57BL6 mice (WT) to assess APL expression. Next, naïve T cells isolated from WT were adoptively transferred into Rag-deficient mice (Rag −/− ) to induce chronic colitis, followed by isolation of splenic and colonic CD4 + T cells from these T-cell-reconstituted Rag −/− to compare with those of WT. In addition, WT naïve T cells were differentiated into either Th1, Th2, or Th17 in vitro to analyse APL expression. Finally, the Rag −/− receiving naïve T cells were administered synthetic APL peptide to assess the severity of colitis. Results: Semi-quantitative PCR (qPCR) revealed that CD4 + T cells express relatively higher level of APL compared with other cell types including the epithelia in colonic tissue from WT. However, APL expression in the colonic tissues from the Rag −/− induced chronic colitis was unexpectedly down-regulated compared with those without colitis, which is not consistent with the previous report using acute DSS colitis model. Subsequently, qPCR revealed significantly decreased APL expression in the splenic and colonic T cells from Rag −/− -induced colitis compared with that of WT. APL expressions in all of the differentiated T cells in vitro, such as Th1, Th2, and Th17, were also significantly down-regulated compared with that of non-differentiated control. Given these results, synthetic APL peptide was injected into the Rag −/− that underwent T-cell reconstitution to antagonise the APL down-regulation. This resulted in reduced severity of colitis compared with that of vehicle-injected control. Conclusions: These results suggest that T cells can be one of the major sources of APL in colonic tissues, and APL down-regulation in effecter T cells may lead to the development of chronic colitis. In addition, APL may be a novel therapeutic target for IBD.